The Effect of Career Development and Work Discipline to Job Satisfaction of Programming Department Employees at PT. X - Anti Purnamasari; Agung Wahyu Handaru; Widya Parimita (LPPM Universitas Negeri Jakarta, 2021)
The purpose of this study was to determine the effect of Career Development and Work Discipline on the work of Programming employees at PT. X. The subject of this research is PT. X, which is one of the private TV stations in Indonesia and located in Jakarta. The population of this study was 116 people, and the sampling method used was saturated sampling, so the number of samples in this study was also 116 people. This research used the multiple linear regression analysis method in analyzing research data. The results showed that Career Development and Work Discipline had a significant positive effect on work, either separately or simultaneously. This implies that if there is an increase of career development and/or employees’ work discipline, the job satisfaction felt by employees will also increases.